Development Of Sekaa Selonding Manik Selukat Banjar Tunjuk Kelod | Pembinaan Sekaa Selonding Manik Selukat Banjar Tunjuk Kelod - I Wayan Yoko Mahase Putra (GHURNITA: Jurnal Seni Karawitan, 2023)
Selonding is a traditional Balinese musical instrument older than other gamelans, which is now widespread in art and traditional and religious ceremonies. The word Selonding is thought to have come from the words "salon" and "ning," which mean a holy place because, judging from its function, it is a gamelan that is sacred or purified. Another opinion also states that Selonding comes from the words "saron" and "ding," which means the gamelan blades with the lowest tone, namely the ding tone. The formulation of the problem that the author designed included increasing youth interest in playing Selonding, what techniques and methods were used, and what benefits were obtained. In coaching Gending Selonding, which is the main work program of the author himself, the author presents the Gilak Ngundang Ujan, Sekar Gadung, and Rejang Lente buildings. In practice, the author invites teenagers from several Banjars within the scope of Tunjuk Village. From the coaching of Gamelan Selonding percussion in Tunjuk Village, it is hoped that it can contribute and be of good use to the Village and the youth participating in these activities. Apart from that, after coaching on beating the Selonding Gamelan, it can be helpful if there is a religious ceremony around or outside the Village.